377 Sentinel node detection in gynecology oncology: our experience with indocyanine green (ICG). (18th September 2019) - Nico, A; Lay, L; Zeff, N; Sanchez, A; Cuellar, S; San Martín, G; Zarlenga, C; Lupo, E; Gianni, S; Ostojich, M
Abstract : Objectives: Sentinel node (SLN) technique has been able to reduce full lymphadenectomy associated morbidity. The introduction of indocyanine green (ICG) has shown improved SLN detection rates. The purpose of this study was to examine the feasibility of SLNs detection in Gynecologic Cancers: Cervical(UCC) Endometrial(EC) and Vulvar Cancer(VC); using ICG, patent blue(PB) and tc99 radiocolloid (tc99m). We evaluated overall and bilateral detection rate for each tracer. Methods: Between January 2017 and March 2019, 21 patients were scheduled for SLN detection (16 CCU, 2 VC and 3 EC). For CCU and EC 500μCi of tc99m were injected at each quadrant of the cervix and lymphoscintigraphy were performed the day before surgery. VC injections were preformed around the tumor. Immediately before surgery 2ml of patent blue and 2ml of ICG were injected at the same positions. SLNs were identified using a NIR fluorescence, radioactive guidance and direct vision. Results: Three tracers were used in 76% of the cases, all had at least two. Detection rate was 100% for 3 methods combined: ICG 100%, Tc99m 100%, PB 77%. Bilateral detection was 100% for 3 methods combined: ICG 88%, Tc99m 88%, PB 38%. No adverse effects related to either tracer were shown. Conclusions: Our study is the first reported experience in Argentina to compare ICG to gold standard tc99m for the detection of SLN in Gynecologic Cancers. ICG sensibility rate is comparable to tc99m, adding the possibility of direct visualization during the procedure. The later facilitates surgeons' task reducing morbidity and surgical duration.